Translating Sexuality Education in Ethiopia and Kenya: A Multi-Sited Approach. Issue 2 (3rd July 2021) - Kolah Ghoutschi, Sara; Aldape, Alina de Luna; Bonacker, Thorsten
Abstract : In this article, we explore how comprehensive sexuality education ('CSE') is being translated across different sites in Ethiopia and Kenya. The comprehensive approach to sexuality education is seen as both a tool for implementing numerous internationally established rights around sexuality and reproduction and it is also increasingly recognised as a human right on its own alongside the right to health and education. However, it is strongly contested by various actors and on multiple sites in terms of its claim of being culturally relevant and sensitive and it is also instrumentalised as a norm-spoiling tool used to contest related norms around sexual and reproductive health and rights ('SRHR'). With this empirical study, we contribute to research on the translation of contested norms and ideas in different contexts. We problematise the difficulties of the universal language underlying human rights approaches and the ambiguity of comprehensive sexuality education when considering the extent to which CSE can develop emancipatory potential through translation. Focusing on the practices of translation among and within these different transnational sites, we examine where and how contested norms such as CSE are translated, arguing that a focus on researching sites of translations allows us to grasp the varieties of translation.